Raising the dead: on brands that go bump in the night. Issue 5 (24th March 2021) - Brown, Stephen; Patterson, Anthony; Ashman, Rachel
ABSTRACT: Many brands have been obliterated by the 'death of the high street' and many more have had near-death experiences. This paper applies Derrida's 'hauntology' to Hollister, a high-flying fashion brand that fell from grace. Although it remains in the land of the living, selling impossible dreams of So-Cal's beachside lifestyle, Hollister is a ghost of its former self. An interpretive empirical investigation reveals that the brand's hauntology comprises four phantomic components: mortality, anxiety, liminality and retroactivity . A spectral 'model' of bump-in-the-night brands also makes its presence felt. At a time when the spectre of pandemic is stalking retail branding, this paper considers Derrida's incongruous, possibly prescient, claim that 'the future belongs to ghosts'. With the aid of interpretive empirical research, we investigate this haunting hypothesis. And although the findings don't confirm Derrida's contention that the dead can often be more powerful than the living, they show how the spectral side of branding gives ghosts a chance to shine.